Discussion of: “Investor protection under unregulated financial reporting” (by Jan Barton and Gregory Waymire) - Leftwich, Richard (Journal of Accounting and Economics, 2004)
Barton and Waymire (J. Account. Econ. (this issue)) investigate voluntary accounting disclosure practices in the 1920s. They conclude that managers’ incentives explain, in part, cross-sectional reporting differences. Moreover, the authors conclude that firms with higher “quality” financial reporting experienced substantially lower price declines when stock prices dropped so dramatically in October 1929. Their first finding seems incontrovertible, albeit less surprising. Their second finding is more ambitious, but is questionable, given the limitations of the theory and the empirical tests they employ.